Repurposing Metformin: Potential as a Prevention, Treatment and Adjunct Therapy in Pancreatic Cancer - Kamizela, Emilia; Rudzińska, Anna; Ponikowski, Kacper; Wrzosek, Kacper; Gumółka, Paulina; Oberda, Jakub; Paluch, Alicja; Haba, Sylwia; Jakubik, Karol; Kolasa, Eliza; et al. (Quality in Sport, 2024)
Metformin, a widely prescribed treatment for type II diabetes, offers promising benefits beyond glycemic control, including improved lipid profiles and cardiovascular outcomes. It inhibits gluconeogenesis in the liver by activating AMPK, thereby reducing glucose production and enhancing glucose uptake in muscle. Recent studies highlight its potential anticancer effects, particularly through the suppression of the mTOR pathway via LKB1-dependent AMPK activation, which inhibits cell proliferation. This review explores metformin’s role as an adjunct therapy in pancreatic cancer, summarizing evidence on its molecular mechanisms and potential efficacy. The findings suggest metformin’s broader therapeutic applications, especially in oncology, warrant further investigation. The aim: The aim of this study is to analyze the role of metformin as an adjunct therapy in the treatment of pancreatic cancer, with particular focus on its molecular mechanisms, such as AMPK activation and mTOR pathway inhibition. The study aims to summarize the current scientific evidence regarding its potential effectiveness.